Proceedings of 35th Biennial Meeting 2009
DOI: 10.5274/assbt.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Headline (pyraclostrobin) as a yield enhancer for sugarbeets in Michigan.

Abstract: Headline is an effective fungicide for controlling Cercospora leafspot. It has also been promoted as a yield enhancer beyond its effect as a fungicide. Some farmers use Headline for this yield improvement on other crops, and a benefit has been found to Headline on sugarbeets in some research in other areas. Michigan Sugar Company has tested this claim for four years and Sugarbeet Advancement tested two locations for one year. Methods:Michigan Sugar Company research compared Headline to Eminent, and other Strob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The other sugar beet production area in the United States where growers routinely apply fungicides for CLS control is Michigan. Hubbell et al (13) reported that strobilurin (pyraclostrobin and azoxystrobin) and tetraconazole fungicides, applied at different times prior to harvest, but after other fungicides were used to control CLS, did not enhance yield in Michigan. In Idaho, CLS is not a major problem for growers.…”
Section: Resultsmentioning
confidence: 99%
“…The other sugar beet production area in the United States where growers routinely apply fungicides for CLS control is Michigan. Hubbell et al (13) reported that strobilurin (pyraclostrobin and azoxystrobin) and tetraconazole fungicides, applied at different times prior to harvest, but after other fungicides were used to control CLS, did not enhance yield in Michigan. In Idaho, CLS is not a major problem for growers.…”
Section: Resultsmentioning
confidence: 99%